2019
DOI: 10.14740/jocmr3649
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Primitive Hypoglossal Artery Associated With Multiple Cerebral Aneurysms

Abstract: Persistent primitive hypoglossal artery is a rare anastomosis between the carotid and basilar arteries, and sometimes associated with cerebral aneurysms. However, association of persistent primitive hypoglossal artery with aneurysms located on arteries other than persistent primitive hypoglossal artery itself or posterior circulation is very rare. An 80-year-old woman suffered from subarachnoid hemorrhage, whose angiography demonstrated aneurysms on the left middle cerebral artery and anterior communicating ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 11 publications
0
13
0
1
Order By: Relevance
“…Primitive arteries like the trigeminal artery, auricular artery, hypoglossal artery, as well as anterior atlantoaxial intersegmental artery form the transient vascular anastomotic pathways from the superior to the inferior parts between the primitive carotid and vertebrobasilar arteries during the development of the embryonic craniocerebral circulation [9,14,16] . These vascular anastomoses gradually degenerate and disappear [8,16] . If they do not degenerate and persist into birth or even adulthood, they can become permanent carotid-vertebrobasilar anastomoses [9,14,16] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Primitive arteries like the trigeminal artery, auricular artery, hypoglossal artery, as well as anterior atlantoaxial intersegmental artery form the transient vascular anastomotic pathways from the superior to the inferior parts between the primitive carotid and vertebrobasilar arteries during the development of the embryonic craniocerebral circulation [9,14,16] . These vascular anastomoses gradually degenerate and disappear [8,16] . If they do not degenerate and persist into birth or even adulthood, they can become permanent carotid-vertebrobasilar anastomoses [9,14,16] .…”
Section: Discussionmentioning
confidence: 99%
“…PPHA normally originates from the cervical segment of the ICA, at the plane of the C1–C3 vertebral bodies [4,9,14,16] . After entering the skull through the hypoglossal canal and anastomoses with the basilar artery, PPHA becomes the only artery to supply the basilar artery [8,9,14,16] . Its presence commonly concurs with the dysplasia of the posterior communicating arteries as well as vertebral arteries [9,14,16] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past reviews reported that 26%–27.6% had aneurysms and that were located mainly (about 85%) in the posterior circulation, especially at the PPHA-BA junction. [ 7 10 11 12 13 ] Some of them caused cerebral infarction or subarachnoid hemorrhage and required surgical treatment. Recently, neuroendovascular therapy has tended to be selected, such as mechanical thrombectomy, carotid artery stenting, or intraaneursymal coiling.…”
Section: Discussionmentioning
confidence: 99%